2023
DOI: 10.3389/fphar.2023.1074837
|View full text |Cite
|
Sign up to set email alerts
|

Linggui Zhugan Decoction activates the SIRT1-AMPK-PGC1α signaling pathway to improve mitochondrial and oxidative damage in rats with chronic heart failure caused by myocardial infarction

Abstract: Objective: To investigate the effects of Linggui Zhugan Decoction on mitochondrial and oxidative damage in rats with chronic heart failure after myocardial infarction and the related mechanisms.Methods: Chronic heart failure after myocardial infarction was established by coronary artery ligation. Heart failure rats were randomly divided into three groups: Model group (n = 11), Linggui Zhugan Decoction group (n = 12), and captopril group (n = 11). Rats whose coronary arteries were only threaded and not ligated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 51 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Chen et al ( 98 ) established a CHF model of cardiac hypertrophy induced by AAS and found that Qishenyiqi dropping pills (QSYQ) can significantly inhibit the progression of cardiac hypertrophy to HF induced by AAS in rats; its mechanism is related to the improvement of energy metabolism, oxidative stress, apoptosis, and other pathways. Lingguizhugan decoction can affect the SIRT1-AMPK-PGC-1α pathway, restore mitochondrial membrane potential, reduce ROS and malondialdehyde (MDA) levels, alleviate mitochondria and oxidative stress damage, promote mitochondrial biogenesis, increase the ejection fraction, and improve cardiac function in rats with HF ( 99 ). At the same time, it also antagonizes oxidative stress damage through the Nrf2/Keap1/HO-1 pathway ( 100 ).…”
Section: The Mechanism Of Tcm In Treating Refractory Heart Failurementioning
confidence: 99%
“…Chen et al ( 98 ) established a CHF model of cardiac hypertrophy induced by AAS and found that Qishenyiqi dropping pills (QSYQ) can significantly inhibit the progression of cardiac hypertrophy to HF induced by AAS in rats; its mechanism is related to the improvement of energy metabolism, oxidative stress, apoptosis, and other pathways. Lingguizhugan decoction can affect the SIRT1-AMPK-PGC-1α pathway, restore mitochondrial membrane potential, reduce ROS and malondialdehyde (MDA) levels, alleviate mitochondria and oxidative stress damage, promote mitochondrial biogenesis, increase the ejection fraction, and improve cardiac function in rats with HF ( 99 ). At the same time, it also antagonizes oxidative stress damage through the Nrf2/Keap1/HO-1 pathway ( 100 ).…”
Section: The Mechanism Of Tcm In Treating Refractory Heart Failurementioning
confidence: 99%
“…Their findings demonstrated that lncRNA SNHG8 not only emerged as a risk factor for MI but also exhibited substantial diagnostic potential. Furthermore, extensive transcriptomic studies have revealed a significant correlation between the abnormal expression of inflammation-related genes, such as VEGFA ( 102 ), TNF ( 103 ), IL6 ( 103 , 104 ), IL6R ( 104 ), PTGS2 ( 105 ), immune response-related genes including CDKN2B ( 106 ), CDKN1C ( 107 ), TLR2 ( 108 ), TLR4 ( 108 ), apoptosis and proliferation-related genes like F3 ( 109 ), BTG2 ( 110 ), TXNIP ( 111 ), SAMSN1 ( 112 ), lipid metabolism-related genes such as PPARGC1A ( 113 ), ACSL1 ( 114 ), ABCG1 ( 115 ), SULT2B1 ( 116 ), and extracellular matrix (ECM) and collagen-related genes, such as MMP2 ( 117 ), MMP9 ( 117 ), LTBP4 ( 118 ), TNXB ( 118 ), and the occurrence and development of MI. These findings offer crucial insights into a deeper comprehension of the mechanisms underlying MI and hold promise for the development of more precise approaches for preventing and treating heart disease in the future.…”
Section: Single-omics Approachesmentioning
confidence: 99%
“…17,18 Numerous pharmacological studies have shown that Chinese medicines have the advantages of good safety and precise efficacy in the prevention and treatment of HF, and the AMPK signalling pathway is one of the key pathways through which the active ingredients of Chinese medicines and Chinese medicinal extracts can play a role in improving the outcomes in HF. [19][20][21] This article will review the existing pharmacological and experimental research results of TCM intervention in AMPK signalling pathway to improve HF in recent years.…”
Section: Introductionmentioning
confidence: 99%